Methodological strategies and barriers in teaching EFL of Thai students by Indonesia preservice teachers during the international teaching practice program - Nadila Natasya; Rita Harisma (JPGI (Jurnal Penelitian Guru Indonesia), 2025)
Teaching English as a Foreign Language (EFL) across cultures presents unique challenges, especially when Indonesian pre-service teachers instruct Thai students who face linguistic and cultural barriers in speaking. Storytelling is recognized as an innovative strategy to enhance fluency, vocabulary, and confidence in communication. This study aims to examine the methodological strategies, barriers, and innovations applied by Indonesian pre-service teachers during the International Teaching Practice Program at Thammasat Wittaya School. Using a descriptive qualitative design, data were collected through interviews, classroom observations, and documentation, and analyzed using Miles, Huberman, and Saldana’s (2014) framework. Findings reveal that storytelling served as the main strategy, implemented through teacher-modeled narration, group projects, multimedia aids, and culturally responsive materials. These approaches improved students’ speaking skills, increased participation, and built confidence. However, several barriers emerged, including limited vocabulary, pronunciation difficulties, passive learning preferences, and resource constraints. Teachers addressed these by scaffolding, providing motivational support, and integrating familiar cultural content to sustain engagement. In conclusion, storytelling proved effective in supporting Thai students’ speaking development while helping pre-service teachers adapt to cross-cultural teaching contexts. The study highlights the importance of innovative, student-centered strategies and intercultural competence in preparing future teachers for global classrooms.